Can team-based care improve patient satisfaction? A systematic review of randomized controlled trials. - Jin Wen; Kevin A Schulman (PLoS ONE)
Background Team-based approaches to patient care are a relatively recent innovation in health care delivery. The effectiveness of these approaches on patient outcomes has not been well documented. This paper reports a systematic review of the relationship between team-based care and patient satisfaction. Methods We searched MEDLINE, EMBASE, Cochrane Library, CINAHL, and PSYCHOINFO for eligible studies dating from inception to October 8, 2012. Eligible studies reported (1) a randomized controlled trial, (2) interventions including both team-based care and non-team-based care (or usual care), and (3) outcomes including an assessment of patient satisfaction. Articles with different settings between intervention and control were excluded, as were trial protocols. The reference lists of retrieved papers were also evaluated for inclusion. Results The literature search yielded 319 citations, of which 77 were screened for further full-text evaluation. Of these, 27 articles were included in the systematic review. The 26 trials with a total of 15,526 participants were included in this systematic review. The pooling result of dichotomous data (number of studies: 10) showed that team-based care had a positive effect on patient satisfaction compared with usual care (odds ratio, 2.09; 95% confidence interval, 1.54 to 2.84); however, combined continuous data (number of studies: 7) demonstrated that there was no significant difference in patient satisfaction between team-based care and usual care (standardized mean difference, -0.02; 95% confidence interval, -0.40 to 0.36). Conclusions Some evidence showed that team-based care is better than usual care in improving patient satisfaction. However, considering the pooling result of continuous data, along with the suboptimal quality of included trials, further large-scale and high-quality randomized controlled trials comparing team-based care and usual care are needed.